Prevalence and predictors of tobacco smoking among university students in Sylhet Division, Bangladesh - Hassan, Muhammad Shaikh; Hossain, Md Kamrul; Khan, Hafiz T A (Oxford Academic, 2022)
This article was published in the International Health [© The Author(s) 2018. Published by Oxford University Press on behalf of Royal Society of Tropical Medicine and Hygiene. All rights reserved. ] and the definite version is available at: https://doi.org/10.1093/inthealth/ihy091 The Journal's website is at: https://academic.oup.com/inthealth/article/11/4/306/5229283?login=false